2022
DOI: 10.3389/fcell.2022.883523
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein Signaling in Cancer; Some Topics in the Recent 10 Years

Abstract: Bone morphogenetic proteins (BMPs), members of the transforming growth factor-β (TGF-β) family, are multifunctional cytokines. BMPs have a broad range of functions, and abnormalities in BMP signaling pathways are involved in cancer progression. BMPs activate the proliferation of certain cancer cells. Malignant phenotypes of cancer cells, such as increased motility, invasiveness, and stemness, are enhanced by BMPs. Simultaneously, BMPs act on various cellular components and regulate angiogenesis in the tumor mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 159 publications
(215 reference statements)
1
27
0
Order By: Relevance
“…Whether BMP is a tumor suppressor or promoter in CRC is controversial [5][6][7][8] . Such complexities in BMP signaling have been described in various cancers 9,10 . As CRC organoids exhibited varying responses to BMP inhibition in our study, one possible explanation for the controversy regarding the role of BMP in CRC is the heterogeneous nature of the disease.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Whether BMP is a tumor suppressor or promoter in CRC is controversial [5][6][7][8] . Such complexities in BMP signaling have been described in various cancers 9,10 . As CRC organoids exhibited varying responses to BMP inhibition in our study, one possible explanation for the controversy regarding the role of BMP in CRC is the heterogeneous nature of the disease.…”
Section: Discussionmentioning
confidence: 95%
“…More recently, Yokoyama et al reported that autocrine BMP4 signaling is a therapeutic target in CRC cell lines 8 . In addition to the context dependencies of the BMP effect that have been discussed in various cancers 9,10 , these controversies might represent inter-tumor heterogeneity among the CRC population. One possible explanation for the latter is that the mutation status of SMAD4 and TP53 is suggested to determine cell fate by BMP 11 .…”
Section: Introductionmentioning
confidence: 99%
“…BMP4 also contribute to neural development. BMPs interact with K-RAS and are upregulated in NSCLC [232]. The BMPs are also involved in adult tissue homeostasis.…”
Section: Role In Proliferation Differentiation and In Tumorigenesismentioning
confidence: 99%
“…DIPG is a result of genetic mutations (K27M) on the ACVRI/ALK2 gene locus encoding the serine/threonine kinase ALK2 resulting in single amino acid substitution -lysine to methionine (55,73). Interestingly, these somatic ACVR1 mutations in DIPG are identical to germline mutations found in FOP (55,74,75). Many DIPG tumors are exploiting Cordin-like-1 (CHRDL1) capacity to hijack BMP ligands.…”
Section: Bmps In Cancermentioning
confidence: 99%